Saudo Arabijos žurnalisto Jamalio Khashoggio bylos nagrinėjimas „Al Jazeera“ pokalbių laidose - Salameh, Rasha A. (Žurnalistikos tyrimai, 2019)
This paper attempts to evaluate Al-Jazeera Arabic Channel talk shows’ treatment of the Saudi journalist Jamal Khashoggi’s case by posing two main questions: the first deals with the amount of coverage granted to this issue. One of the research hypotheses arises here, namely that the coverage was remarkably intense, which may be explained by Al-Jazeera’s dedicated position on the issue. This is explored in this paper through analysis of content and by interviewing the director of news at Al-Jazeera channel, Asif al-Humaidi, and by surveying previous studies that have linked Al-Jazeera’s previous positions to Qatar’s official stand, particularly that the Khashoggi incident took place in the midst of the Qatari-Saudi political crisis. The research samples include four talk shows: “Without Borders,” “Beyond the News,” “Rest of the Story” and “Scenarios,” over the course of a month since Khashoggi’s disappearance. The analysis shows that Khashoggi’s case received 93% of the total coverage of the four programs during the monitoring period.The second question deals with several items in the professionalism category, in terms of balancing time granted to the guests, and the degree of objectivity shown by the presenters during the dialogue. It was found that the rate of the presenters’ interventions during guests’ presentation was 57%, in addition to temptations utilized during the dialogues. Another question arises regarding the extent of hate speech in these talk shows, which amounts to 69.4%, by analyzing several items, most notably emotional mobilization, which rated 40.7%.